2021
DOI: 10.3390/ijms22031381
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of ANGPT1, CD39, FGF2 and MMP9 Linked to Clinical Outcome of Bevacizumab Plus Chemotherapy for Metastatic Colorectal Cancer

Abstract: Angiogenesis pathway genes show substantial genetic variability causing inter-individual differences in responses to anti-angiogenic drugs. We examined 20 single nucleotide polymorphisms (SNPs) in 13 of these genes to predict tumour response and clinical outcome measured as progression free survival (PFS) and overall survival (OS) in 57 patients with metastatic colorectal cancer (mCRC) given bevacizumab plus chemotherapy. SNPs were detected (iPLEX® Assay) in genomic DNA extracted from formalin-fixed paraffin-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Several studies have shown that CXCL13 is involved to mediate 5-Fu resistance mechanism and considered to be a biomarker for predicting the prognosis of colorectal cancer, which is consistent with our ndings (47,48). FGF2, a member of the broblast growth factor (FGF) family whose signaling network has been implicated in several pathways, such as normal cell growth, differentiation, angiogenesis and tumor development, signi cantly promotes tumor cell differentiation and proliferation (49,50). FGF7, also called keratinocyte growth factor (KGF), is involved in inducing vascular endothelial growth factor (VEGF)-A expression, which plays important roles in the angiogenesis and metastasis of various cancer cells including colorectal cancer (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that CXCL13 is involved to mediate 5-Fu resistance mechanism and considered to be a biomarker for predicting the prognosis of colorectal cancer, which is consistent with our ndings (47,48). FGF2, a member of the broblast growth factor (FGF) family whose signaling network has been implicated in several pathways, such as normal cell growth, differentiation, angiogenesis and tumor development, signi cantly promotes tumor cell differentiation and proliferation (49,50). FGF7, also called keratinocyte growth factor (KGF), is involved in inducing vascular endothelial growth factor (VEGF)-A expression, which plays important roles in the angiogenesis and metastasis of various cancer cells including colorectal cancer (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Many kinds of drugs are used to treat tumours. For example, bevacizumab is used to treat advanced ovarian cancer, 39 metastatic colorectal cancer 40 and non-small cell lung cancer. 41 Bicalutamide is used to treat metastatic hormone-sensitive prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…27 Fortunately, we found that Maria Gaibar and colleagues explored in 2021 that polymorphisms of angiogenesis pathway genes (ANGPT1, CD39, FGF2, and MMP9) were associated with clinical outcome of bevacizumab plus chemotherapy for metastatic colorectal cancer. 19 EJ Lewintre and colleagues reported recently that polymorphism of VEGFR-1 and VEGF-A and plasma levels of VEGF-A predicted the efficacy and prognosis of patients with nonsquamous NSCLC receiving chemotherapy combined with bevacizumab administration. 28 Collectively, polymorphism in the gene at the pathway single of bevacizumab disposition was proved to be of certain clinical significance for bevacizumab-based regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study was designed as a real-world retrospective study just as the previous polymorphism study regarding bevacizumab-based therapy did. 19…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation